2022
DOI: 10.1007/978-3-031-09593-1_21
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Well-Being Through Conversational Coaching for Active and Healthy Ageing

Abstract: With life expectancy growing rapidly over the past century, societies are being increasingly faced with a need to find smart living solutions for elderly care and active ageing. The e-VITA project, which is a joint European (H2020) and Japanese (MIC) funded project, is based on an innovative approach to virtual coaching that addresses the crucial domains of active and healthy ageing. In this paper we describe the role of spoken dialogue technology in the project. Requirements for the virtual coach were elicite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The evaluation of a preliminary system focused on user expectations and showed that users have a positive opinion of the coaching system and strongly desire the information to be tailored to their daily lives [ 35 ]. More aspects of the system are detailed in [ 5 , 60 , 61 ], underscoring the testing methodology that involves a thorough process of gathering requirements for the virtual coach. This process incorporates interviews and participatory design in real-life settings, reflecting a user-centric approach that ensures alignment with the specific needs and preferences of older adults.…”
Section: Platform Componentsmentioning
confidence: 99%
“…The evaluation of a preliminary system focused on user expectations and showed that users have a positive opinion of the coaching system and strongly desire the information to be tailored to their daily lives [ 35 ]. More aspects of the system are detailed in [ 5 , 60 , 61 ], underscoring the testing methodology that involves a thorough process of gathering requirements for the virtual coach. This process incorporates interviews and participatory design in real-life settings, reflecting a user-centric approach that ensures alignment with the specific needs and preferences of older adults.…”
Section: Platform Componentsmentioning
confidence: 99%
“…Hence, new, innovative and tailored prevention solutions are needed to support the care and well-being of older people. The e-VITA project "EU-Japan Virtual Coach for Smart Ageing" (H2020-SC1-DTH-04) presents an innovative virtual coaching approach that addresses the domains of Active and Healthy Ageing (AHA) and Active and Assisted Living (AAL) in terms of cognition, physical activity, mobility, mood, social interaction, leisure, and spirituality, with the aim of empowering older people to better manage their health and daily activities, resulting in improved well-being and stakeholder collaboration [1], [2]. The e-VITA virtual coach offers personalized recommendations based on the analysis of data collected from wearable devices and non-intrusive sensors placed in the smart living environment [3] and provides support through natural language interaction with holograms, emotional objects or robots [4].…”
Section: Introductionmentioning
confidence: 99%